2019
DOI: 10.1101/766659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basal forebrain parvalbumin neurons mediate arousals from sleep induced by hypercarbia or auditory stimuli

Abstract: SUMMARYBrief arousals from sleep in patients with sleep apnea and other disorders prevent restful sleep, and contribute to cognitive, metabolic and physiologic dysfunction. Little is currently known about which neural systems mediate these brief arousals, hindering the development of treatments. The basal forebrain (BF) receives inputs from many nuclei of the ascending arousal system. These inputs include the brainstem parabrachial neurons which promote arousal in response to e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 33 publications
(7 reference statements)
2
22
0
Order By: Relevance
“…Additionally, there was a robust, long-lasting NREM sleep fragmentation and state instability resembling the disrupted sleep pattern observed in sleep apnea (Guilleminault et al, 1976;Kimoff, 1996), Alzheimer's disease (Lim et al, 2014), and aging (Lim et al, 2014;Li et al, 2018). Similarly, chemogenetic stimulation of cholinergic neurons in the basal forebrain, lateral to the preoptic area, increases wakefulness and fragments sleep (Anaclet et al, 2015) and optical stimulation of basal forebrain parvalbumin neurons induces brief, rapid arousals from sleep (McKenna et al, 2020). Relative to basal forebrain glutamatergic neurons, optogenetic stimulation increases wakefulness (Xu et al, 2015), whereas activation of these neurons using chemogenetic strategies did not significantly alter sleep-wake states (Anaclet et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, there was a robust, long-lasting NREM sleep fragmentation and state instability resembling the disrupted sleep pattern observed in sleep apnea (Guilleminault et al, 1976;Kimoff, 1996), Alzheimer's disease (Lim et al, 2014), and aging (Lim et al, 2014;Li et al, 2018). Similarly, chemogenetic stimulation of cholinergic neurons in the basal forebrain, lateral to the preoptic area, increases wakefulness and fragments sleep (Anaclet et al, 2015) and optical stimulation of basal forebrain parvalbumin neurons induces brief, rapid arousals from sleep (McKenna et al, 2020). Relative to basal forebrain glutamatergic neurons, optogenetic stimulation increases wakefulness (Xu et al, 2015), whereas activation of these neurons using chemogenetic strategies did not significantly alter sleep-wake states (Anaclet et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study we showed that BF-PV neurons fulfil the criteria for a system which responds to danger signals during sleep by transiently enhancing alertness to support appropriate responses to threat 19,54 . Our results here show that during wake BF-PV neurons are important for vigilant attention in a food-motivated signal detection task.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of other neurochemically defined BF subtypes is unknown. Recent work has shown that one population of BF GABAergic neurons containing the calcium-binding protein parvalbumin (PV) control cortical fast oscillations and arousals from sleep [16][17][18][19] but their role in awake behavior is unclear. Thus, here we test the hypothesis that BF-PV neurons modulate vigilant attention in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; McKenna et al . 2020). BF inhibition impairs arousal not only to CO 2 , but also to an auditory stimulus, which is consistent with the regulation of cortical excitability in general (McKenna et al .…”
Section: Role Of Subcortical Arousal‐promoting Structures In the Co2 Arousal Reflexmentioning
confidence: 99%